Dust cleaning robots (DCR) for BIPV and BAPV solar power plants-A conceptual framework and research challenges - Kumar, Nallapaneni Manoj; Sudhakar, K.; Mahendran, Samykano; Sukumaran, Sreenath (Elsevier, 2018)
This paper proposes a conceptual framework to design and develop robots for addressing the soiling or the dust cleaning issue on the building integrated photovoltaics (BIPV) and building applied photovoltaics (BAPV). BIPV and BAPV turn the present and future buildings (high rise or low rise) into power stations with the introduction of photovoltaics either in the façade (90° wall) or roof (flat or pitched) configuration. But one of the significant challenges that influence the energy performance is the dust accumulation. This is a serious issue in the places where air pollution is very high. Addressing this would be very difficult for the human workforce, and the complexity and tediousness would increase depending on the size of the BIPV and BAPV array or the height of the building. Currently, there are few dust cleaning robots which could offer services in addressing the soiling issues in conventional photovoltaic installations. The existing dust cleaning robots (DCR) could not offer a better feasible solution in BIPV and BAPV as they offered in traditional PV systems that were installed in an open area. Hence for addressing dust cleaning issue, some novel conceptual schemas related to robot developments were proposed in this paper considering the installation configuration of PV systems for building applications. Here, DCR’s for three configuration of PV installation with building applications namely BIPV/BAPV façade, BIPV/BAPV horizontal roof, and BIPV/BAPV pitched roof are dealt. The proposed conceptual robots were briefly described with the schematic views highlighting operation, energy consumptions, and slipping issue etc. Scope for the development and various research challenges that are to be considered during the design stage are highlighted along with the discussion